Aspartate beta-hydroxylase is a prognostic factor in gallbladder cancer with the function of promoting tumorigenesis and chemoresistance - Yuan, Luo; Yunpeng, Huang; Xiong, Li; Wen, Yu; Yongxiang, Wang (Frontiers in Endocrinology, 2025)
AimsGallbladder cancer is characterized by a dismal prognosis, with a limited number of biological markers currently identified for the carcinogenesis, progression and prognosis of gallbladder cancers (GBCs). The discovery of efficacious biomarkers is crucial for enhancing the prognosis of gallbladder cancer.MethodsAnalysis of RNAseq datasets from gallbladder cancer allowed the identification of differential genes between gallbladder cancer and adjacent tissues. Subsequent application of Mendelian randomization extracted target gene known to promote gallbladder cancer from these differentially expressed genes. Immunohistochemistry was then conducted to evaluate the expression of these target gene in a cohort of 215 patients with gallbladder cancer, utilizing follow-up information to determine their prognostic value. Moreover, single-cell sequencing data of gallbladder cancer elucidated the role of target genes within the immune microenvironment of this cancer type. The Genomics of Therapeutics Response Portal (CTRP) database enabled the assessment of the impact of target genes on the IC50 of chemotherapy drugs. Lastly, network pharmacology and analytical methodologies were employed to investigate the effects of traditional Chinese medicine active ingredients targeting these specific genes.ResultsASPH expression is notably elevated in gallbladder cancer tissues, correlating with an unfavorable prognosis for patients afflicted with this disease. Results from Mendelian randomization studies suggest that heightened ASPH levels play a significant role in the development of gallbladder polyps and stones, which are established clinical risk factors in gallbladder cancer. Analysis of clinical samples demonstrates a positive association between ASPH expression and indicators of poor differentiation, increased tumor size, advanced TNM stage, lymph node metastasis, and invasion. The single-cell immune microenvironment reveals that ASPH not only enhances the expression of immune checkpoints, namely PDL1 and PVR, in the gallbladder cancer epithelium, resulting in immune evasion, but also triggers epithelial-mesenchymal transition and migration, promoting metastasis. Furthermore, ASPH contributes to heightened tumor drug metabolism, hence raising the IC50 values for gemcitabine and paclitaxel. Utilizing network pharmacology and molecular docking techniques, this study pinpointed six bioactive compounds derived from traditional Chinese medicine with a targeted effect on the ASPH protein, comprising Sebacic acid, Suberic acid, Azelaic acid, Dimelic acid, Succinic acid, and D-Asparaginsaeure.ConclusionsASPH plays a role in promoting the development of gallbladder cancer and resistance to chemotherapeutic agents, rendering it a promising target for therapeutic interventions. Active therapeutic compounds targeted on ASPH can be identified among the active ingredients present in traditional Chinese medicine.